Strategi dalam Mengatasi Tingkat Kecemasan Akademik Siswa Menjelang Pelaksanaan Ujian Berbasis Cognitive Behavioral Therapy (CBT) - Nadya Ramadinah; Tastiara Tastiara; Dhieta Rizky Palupi Prameswari; Annisa Nasywa Kalyca; Ratna Sari Dewi (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2025)
Academic anxiety is a prevalent concern encountered by students before to examinations, which may adversely affect academic performance. This article aims to illustrate successful approaches derived from the Cognitive Behavioural Therapy (CBT) approach to mitigate students' academic anxiety. The used process may include a literature evaluation by examining 20 relevant and cohesive periodicals. The findings demonstrate that CBT therapies, including individual or group counselling, self-talk techniques, progressive muscle relaxation, and systematic desensitisation, are very successful in reducing student anxiety. Cognitive Behavioural Therapy enables students to identify and modify negative thought patterns that provoke anxiety into more rational and adaptive thinking. By implementing appropriate methods, students may prepare for examinations with more tranquilly and confidence. This article is anticipated to be a valuable reference for school counsellors and educators in developing mental intervention programmes to enhance kids' overall well-being.